Tourism, travel and COVID-19 : the new narrative for Southern and Eastern Africa during a crisis vortex - Hebbard, Shanaleigh (Knowledge Resources, 2020)
The outbreak of COVID-19 forced the hospitality industry in Southern and Eastern Africa to lock its doors, which led to millions of cancelled bookings and billions lost in revenue. In a world of uncertainty, complexity, unpredictability and information overload, this book cuts through the clutter and panic and calmly leads you from being stuck and in survival mode to inspired action and developing a thriving mindset.The New Narrative for Southern and Eastern Africa provides stories, insights, guidelines and toolkits from 24 leading experts in the tourism and travel industry.